A Small but Spartan Band : The Florida Brigade in Lee's Army of Northern Virginia - Waters, Zack C., 1946- (Book collections on Project MUSE., 2010)
A unit that saw significant action in many of the engagements of the Civil War's eastern theater. Until this work, no comprehensive study of the Florida units that served in Robert E. Lee's Army of Northern Virginia (ANV) had been attempted, and problems attend the few studies of particular Florida units that have appeared. Based on more than two decades of research, Waters and Edmonds have produced a study that covers all units from Florida in the ANV, and does so in an objective and reliable fashion. Drawn from what was then a turbulent a.